MUC460 : Composer colloquium II / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2023)
This course exposes students to musical forms, styles, genres and dimensions of composition, through lectures, analysis and guest presentations by invited speakers. Students freely explore the knowledge gained in class and discuss, analyze and critique different aspects of contemporary composition, lyric writing and performance practices. They plan, research and present their own assignments and exercises on topics discussed in class, including their own viewpoints on the material presented.